Evaluation of the Effectiveness of Technology Transfer in the Process of Wood Crafts for Workers with Disabilities - Sugiono Sugiono; Bayu Rahayudi; Rudianto Raharjo; Dwi H Sulistyarini; Slamet Thohari; Nur M. F. Dinia; Qoid A Fadhlurrahman; Safa S Istafada (ICSE (Institute of Computer Science and Engineering), 2022)
Technological changes are important to increase productivity, quality of products produced, and provide safety and health for workers. The purpose of this paper is to evaluate the application of wood craft machinery technology by persons with disabilities. The first step is an initial survey of the existing wood craft production process, which related to the equipment used, work methods, and work results (productivity and quality) as well as the level of accidents or health problems at work. Small enterprises for disabled workers were used as research objects to check the impact of technological changes on the production process. Changes in technology used in the form of cutting machine, carving chisel, small CNC machine, smoothing machine, and paint machine (finishing process). The Unified Theory of Acceptance and Use of Technology (UTAUT) was adopted to approach the assessment of the impact of the technology implementation of the wood carving process. Data was collected through several activities such as interviews and direct observation. The success measurement parameters were divided into several main points, including performance, effort, user behavior, experience, facility design, environmental impact, and the level of worker safety or health. In short, it can be said that technology can improve the quality and productivity of work for disabled workers while still paying attention to the ergonomic value of the human-machine relationship at the right workstation.